A new epigean harvestman of the genus Guerrobunus (Laniatores: Phalangodidae), from Hidalgo, Mexico, with taxonomic notes about the genus - Cruz-López, Jesús A.; Ubick, Darrell (Zootaxa, 2015)
The fifth species of the genus Guerrobunus, Guerrobunus barralesi sp. nov. is described from specimens collected in Hidalgo, Mexico. This species represents the first eastern record from the country and unlike other species of the genus, is completely epigean. Guerrobunus barralesi sp. nov. is compared with the most similar species, Guerrobunus minutus, which also has well developed and pigmented eyes. Finally, external morphology, including male genitalia, taxonomy of the genus, and familial assignment into the family Phalangodidae are discussed.